دور التحفيزات الجبائية في تفعيل الجباية العادية - حبار حاج محمد ة أمين (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
مستخلص: هدفت هذه الدراسة إلى إبراز دور التحفيزات الجبائية المطبقة في الجزائر في تفعيل وتعزيز الجباية العادية خلال الفترة ( ،)0300-0330وللإجابة على الإشكالية المطروحة تطرقت الدراسة إلى المقاربات النظرية للسياسة الجبائية والنظام الجبائي، بالإضافة إلى استعراض الإطار النظري العام للتحفيزات الجبائية وعلاقته بالاستثمار وترقيته، مع الوقوف على الآليات المعتمدة في منح التحفيزات الجبائية في الجزائر، ومن خلال الدراسة التحليلية، تم تقييم فعالية التحفيزات الجبائية ومساهمتها في تفعيل إيرادات الجباية العادية في الجزائر، بالاعتماد على مختلف البيانات والاحصائيات السنوية للفترة ( ،)0300-0330مع التركيز على تحليل نتائج البيانات المتعلقة بالتحفيزات الجبائية لمديرية كبريات المؤسسات ) (DGEفي إطار الوكالة الجزائرية لترقية الاستثمار ( )AAPIخلال الفترة (-0303 .)0300 توصلت الدراسة من خلال نتائج الدراسة التحليلية، إلى أن التحفيز الجبائي الممنوح أثناء مرحلة إنجاز المشروع في إطار أجهزة دعم الاستثمار، يشكل الحصة الأكبر من الإنفاق الجبائي ويؤثر على المدى القصير في تراجع ايرادات الجباية العادية، لكن بعد انقضاء فترة الانجاز، يتحول التحفيز الجبائي الممنوح سابقا إلى عائد أثناء مرحلة الشروع في الاستغلال، وبالتالي يساهم بشكل فعال في تعزيز ايرادات الجباية العادية. الكلمات المفتاحية: التحفيزات الجبائية؛ الجباية العادية؛ الايرادات الجبائية؛ الانفاق الجبائي؛ المزايا الجبائيةAbstract: This study aimed to highlight the tax incentives applied in Algeria and their role in activating and strengthening regular tax collection during the period (2002-2022). To answer the problem raised, the study addressed the theoretical approaches to tax policy and tax system, in addition to reviewing the general theoretical framework of tax incentives and their relationship to investment and its promotion. As well as determining the mechanisms adopted for granting tax incentives in Algeria. Through the analytical study, the researcher assessed the effectiveness of tax incentives and their contribution to activating regular tax revenues in Algeria based on various annual data and statistics for the period (2002-2022), with the focus on analyzing data related to fiscal incentives for the Directorate of Large Enterprises (DGE) within the framework of the Algerian Agency for Promoting the Investment (AAPI) for the period (2010-2022). Based on the analytical study results, the researcher concluded that tax incentives granted during the project completion phase by the investment support agencies constitutes the largest share of tax spending and affects, in the short term, the decline in regular tax revenues. However, after the completion period has passed, the previously granted tax incentive transforms into revenue during the initiation stage of exploitation. Thus, it contributes effectively to enhancing regular tax collection revenues. Keywords: tax incentives; Regular tax collection; tax revenues; Excise spending; Fiscal Advantages
دراسة حالة الجزائر خلال الفترة 2002-2022
Keywords: التحفيزات الجبائية; الجباية العادية; الإيرادات الجبائية; الإنفاق الجبائي; المزايا الجبائية